Pergeseran Makna Tazkiyatun Nafs Menjadi Tren Self Healing di Era Digital - Indra Kurniawan; Ahmad Sayuti; Aco Karso; Sumadi (Jurnal Pendidikan Agama Islam, 2026)
The digital era has transformed mental health practices, positioning social media as the primary platform where millennials and Gen Z seek emotional support through self-healing trends. However, this trend often reduces the profound concept of inner healing to a form of instant, recreational, and consumptive activity. Utilizing a descriptive qualitative method, this study aims to: map the semantic shift from the Islamic concept of tazkiyatun nafs (purification of the soul) to the digital self-healing trend, analyze the factors driving this conceptual reduction, and propose a reconstructive perspective grounded in tazkiyatun nafs. Data were collected through documentary study of primary and secondary literature and analyzed inductively. The findings reveal that social media frames self-healing as a performative public display, which obscures its essence as a transformative process of introspection and spiritual purification. This shift leads to negative consequences, including superficial relief, spiritual fragility, and a dependence on external validation. As a solution, this study recommends integrating the principles of tazkiyatun nafs specifically the stages of takhalli (emptying vices), tahalli (cultivating virtues), and tajalli (divine illumination), along with practices like muhasabah (self-accounting) and muraqabah (self-awareness) into contemporary digital mental health frameworks. Consequently, this research contributes to restoring depth to the concept of healing by synthesizing Islamic spiritual wisdom with the challenges of mental health in the digital age.